D-Dimers and Fibrinogen in Third Trimester of Normal Pregnancy and Pregnancy Complicated by Gestational Hypertension or Preeclampsia - Kiani, Maha Tariq (International Journal of Pathology, 2023)
Introduction: D-Dimers are very useful for screening thrombotic events as they have high sensitivity because of the high negative predictive value for venous thromboembolism but this increase confounds its use to predict venous thromboembolic events in symptomatic pregnant patients. Objectives: To determine mean levels of D dimers and fibrinogen among pregnant patients in the third trimester and to compare them in normal pregnant women versus pregnant women with gestational hypertension or pre-eclampsia. Material and Methods: This descriptive cross-sectional study was carried out in the Department of Hematology, Holy Family Hospital, Rawalpindi from April 2018 to 30th September 2018.A total of 100 pregnant women; 50 pre-eclamptic and 50 normotensives, 15 to 49 years of age were included. Patients with a family or personal history of thromboembolic disease, varicose veins, any type of malignancy, CLD, and with current infection or fever of >38 °C were excluded. Blood sample from each patient was obtained under aseptic measures by using a 3cc BD syringe. D-dimer concentration was measured on fresh plasma within 4 hours of blood collection, in the D dimer latex kit. The fibrinogen concentration was measured using Clauss fibrinogen assays. Results: In this study, mean levels of D dimers and fibrinogen among pregnant patients in the third trimester were 240.0 ± 112.82 ng/ml and 281.65 ± 51.85 mg/dl. In this study, mean D-dimers during normal pregnancy were 220.0±60.61 ng/ml and in PIH or preeclamptic patients were 260.0±145.69 ng/ml with a p-value of 0.076. Mean fibrinogen levels during normal pregnancy were 280.0±49.72 mg/dl and in PIH or preeclamptic patients were 283.30±54.34 mg/dl with a p-value of 0.752. Conclusion: This study concluded that mean levels of D dimers and fibrinogen in pregnant women with gestational hypertension or pre-eclampsia are higher as compared to normotensives women but the difference is not statistically significant.